2021
DOI: 10.1200/po.21.00104
|View full text |Cite
|
Sign up to set email alerts
|

Association of 17q22 Amplicon Via Cell-Free DNA With Platinum Chemotherapy Response in Metastatic Triple-Negative Breast Cancer

Abstract: PURPOSE To determine whether specific somatic copy-number alterations detectable in circulating tumor DNA (ctDNA) from patients with metastatic triple-negative breast cancer (mTNBC) are associated with sensitivity to platinum chemotherapy. MATERIALS AND METHODS In this secondary analysis of a large cohort of patients with mTNBC whose ctDNA underwent ultralow-pass whole-genome sequencing, tumor fraction and somatic copy-number alterations were derived with the ichorCNA algorithm. Seventy-two patients were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…The detection of specific alterations in ctDNA has shown some important clinical implications. For example, TNBC patients who had 17q22 amplification had better progression-free survival after cisplatin treatment than those without amplification [ 55 ]. The cisplatin favoring effect of 17q22 amplification may be related to the overexpression of some genes in this region, such as KIF2B, TRIM37, NR1D1, and DLX4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detection of specific alterations in ctDNA has shown some important clinical implications. For example, TNBC patients who had 17q22 amplification had better progression-free survival after cisplatin treatment than those without amplification [ 55 ]. The cisplatin favoring effect of 17q22 amplification may be related to the overexpression of some genes in this region, such as KIF2B, TRIM37, NR1D1, and DLX4.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is involved in the G2/M cell cycle checkpoint and inhibition of DNA repair mechanisms and their overexpression can improve the TNBC sensitivity to DNA-damaging platinum chemotherapy [ 51 , 52 , 53 , 54 ]. Collier et al provided an excellent example of chromosome alteration analysis in deepening the implication of 17q22 amplification in plasma samples of 58 TNBC patients treated with cisplatin alone or in combination with paclitaxel [ 55 ]. They proved how the patients that displayed 17q22 amplification had better progression-free survival than the other ones after cisplatin treatment [ 55 ].…”
Section: Liquid Biopsy and Circulating Cell-free Nucleic Acids In Tnbcmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of the ctDNA percentage can help determine tumor dynamics, treatment response, and risk of relapse. ctDNA percentage correlated with progression-free survival in triple-negative breast cancer patients [ 74 , 75 ]. In addition, it can be used to assess specific gene mutations.…”
Section: Ctdna In Metastatic Breast Cancermentioning
confidence: 99%
“…Additionally, Chen et al found that ctDNA mutations offer useful information for evaluating the effectiveness of targeted therapies in breast cancer patients who are resistant to trastuzumab and chemotherapy (Chen et al, 2020). Furthermore, their findings demonstrated that gene amplifications and decreased ctDNA levels were related to higher PFS in patients with advanced TNBC after chemotherapy (Wongchenko et al, 2020;Collier et al, 2021). However, there is a lack of studies predicting the efficacy of ICIs in advanced TNBC through ctDNA detected by NGS.…”
Section: Introductionmentioning
confidence: 99%